ICRRS of manufacturing sector customers of The City Bank Limited – corporate banking division - Ahmed, Sharar Irfan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.